An Analysis of Plots in James W. Ellison “Akeelah and The Bee” - Wibowo, Ari; Lestari, Ayu Rahfiza (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
An Analysis of Plot in James W. Ellison “Akeelah and the Bee”. Thesis English Program of STKIP Muhammadiyah Sorong. The object of the analysis is Plot in the novel Akeelah and the Bee, the plot is taken as data, classified into the kind of plot and analyzed using descriptive analysis method. The purpose of this research is to know the kind of plot in Akeelah and the Bee novel. The result of this research show that in Akeelah and the Bee novel using (Flashback Plot because containing the elements are; Conflict, Exposition I, Exposition II, Exposition III, Exposition IV, Climax I, Climax II and End). And the writer analyze based on the theory of Russel and Freytag. The result of this research can give useful addition information for lecturers, especially in teaching literature about intrinsic element of story. For the students, the result of this research can be used as additional knowledge to improve their knowledge and ability of the literature, especially in plots of story.